ON THE TAPHONOMY OF LATE JURASSIC AND EARLY CRETACEOUS ICHTHYOSAURS FROM THE VOLGA REGION NEAR ULYANOVSK - Efimov V.M. (My University, 2001)
Quantitative data on the finds of bony remains of Late Jurassic and Early Cretaceous marine reptiles in the Volga Region near Ulyanovsk are given. A taphonomic classification of ichthyosaurian fossils and the probable sequence of the disintegration of their skeletons is proposed.
Keywords: Cretaceous; Jurassic; Volga Region; Ichthyosaurs; Mesozoic::Jurassic; Мезозой::Юрская; Мезозой::Меловая; Mesozoic::Cretaceous